2010
DOI: 10.1051/forest/2009125
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhization, growth and nutrition of Pinus halepensis seedlings fertilized with different doses and sources of nitrogen

Abstract: Ann. For. Sci. 67 (2010) Abstract• Although fertilization is commonly used in nurseries, the effects of high level of nitrogen on Pinus halepensis mycorrhization are still unknown.• The effect of fertilization at different N levels (low-LN: 35 mg/plant; medium-MN: 60 mg/plant; high-HN: 120 mg/plant), differing N sources (ammonium-(NH 4 ) 2 SO 4 ; nitrate-HNO 3 ; ammonium+nitrate-NH 4 NO 3 ) and inoculation with Pisolithus tinctorius and Lactarius deliciosus on the mycorrhization, growth and nutrient status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
(41 reference statements)
1
5
0
1
Order By: Relevance
“…In accordance with previous studies, our results show that Pinus seedling growth response to EMF increased with experiment duration (Lekberg and Helgason ) and inoculation of multiple fungal species (Perry et al , Dalong et al ). On the other hand, species mycorrhizal responsiveness decreased with soil fertilization (Browning and Whitney , Diaz et al ) and age of the seedlings when inoculated. We found no conclusive results regarding species responsiveness to EMF inoculation in the native range compared to the introduced range.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous studies, our results show that Pinus seedling growth response to EMF increased with experiment duration (Lekberg and Helgason ) and inoculation of multiple fungal species (Perry et al , Dalong et al ). On the other hand, species mycorrhizal responsiveness decreased with soil fertilization (Browning and Whitney , Diaz et al ) and age of the seedlings when inoculated. We found no conclusive results regarding species responsiveness to EMF inoculation in the native range compared to the introduced range.…”
Section: Discussionmentioning
confidence: 99%
“…Nursery practices must be fine-tuned to encourage colonisation by T. melanosporum, but also to improve vegetative quality of seedlings. However, in nursery fertilisation experiments a conflict between optimal seedling growth and EM colonisation has been reported for many EM fungi (Castellano & Molina 1989, Walker et al 2003, Diaz et al 2010. Two mechanisms have been suggested to explain this conflict: (i) the host reducing carbon supply to the fungus due to a greater carbon demand by growing shoots, or (ii) the fungus requiring most carbon received from the plant to assimilation of the greater N uptake (Wallander 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, Treseder (2004 showed that nitrogen (N) and phosphorus (P) fertilisations decrease mycorrhizal abundance in the field. In nursery experiments, high fertilisation levels have been found to inhibit the formation of ectomycorrhizas of many fungal species including T. melanosporum (Dupré et al 1982, Beckjord et al 1985, Walker et al 2003, Diaz et al 2010, although Castellano & Molina (1989) noticed that some species are much more tolerant and that fertilisation effect was dependent on the application system, fertiliser type, dose and form. On the other side, Quoreshi & Timmer (2000) and Rincon et al (2007) found fertiliser doses that increased growth of containerised conifer seedling without decreasing colonisation levels of inoculated fungi from various EM species.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions with ectomycorrhizae may also explain the absence of effect of leachates supply at low soil fertility. While a high fertilization had been described to be nefast for P. halepensis ectomycorrhizae, at low fertilization level ectomycorrhizae can develop (Diaz et al 2010) and may detoxify phenolic compounds like described on different species (Zeng and Mallik 2006). To our knowledge, no study looked at plant crown architectural response to allelopathy.…”
Section: Interactions With Allelopathic Phenomenonmentioning
confidence: 98%
“…With regard to fertilization, two rates of fertilizer were supplied once by week with irrigation; the first composed of 75 mg N, 8.2 mg P and 20.74 mg K (low fertilization, F-) and the second five times higher (high fertilization F?). Such process and fertilization rates are already used in greenhouse experiment with Aleppo pine saplings (Diaz et al 2010). Finally, the allelopathic factor was tested through the use of leachates (Fernandez et al 2008).…”
Section: Experimental Design and Treatment Applicationmentioning
confidence: 99%